Optimal worst case solutions for state estimation of power system with uncertain network parameters - Rakpenthai C. (2017)
© 2016 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc. This paper addresses the problem of power system state estimation under the condition that transmission line network parameters are unknown but bounded. A robust estimation in the sense of an optimal worst case solution is determined. Data collected via remote terminal units, i.e. voltage magnitude, power flow, and power injection, are used as measurement quantities. The state variables are bus voltage phasors expressed in rectangular coordinates. This makes it possible to express the relations between measured data and state variables as quadratic functions. The proposed formulation based on the structured robust least squares optimization yields a minimization problem with bilinear matrix inequality constraints. A solution method based on semidefinite programming is also presented. Some test results on the standard IEEE test systems are given. © 2016 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.